NOI INIȚIATIVE ALE UNIUNII EUROPENE: PROIECTUL DE COMBATERE A TORTURII ÎN MOLDOVA - Tatiana, Sergheeva, Sosna Boris (SUPREMANCE OF LAW, 2018)
No one shall be subjected to torture or to cruel, inhuman or degrading treatment or punishment (art. 5, Universal Declaration of Human Rights). This article was prepared by the Institute for Democracy (Moldova). This article is funded by the European Union (European Instrument for Democracy and Human Rights). Opinions expressed in the article do not necessarily represent those of the European Union.